Gastric Th17 Cells Specific for H+/K+-ATPase and Serum IL-17 Signature in Gastric Autoimmunity - Della Bella, Chiara; Antico, Antonio; Panozzo, Maria Piera; Capitani, Nagaja; Petrone, Luisa; Benagiano, Marisa; D’Elios, Sofia; Sparano, Clotilde; Azzurri, Annalisa; Pratesi, Sara; Cianchi, Fabio; Ortiz-Princz, Diana; et al. (Frontiers in Immunology, 2022)
Human gastric autoimmunity (AIG) is characterized by inflammation of the gastric mucosa and parietal cells loss. The gastric parietal cell proton pump H+/K+-adenosine triphosphatase (H+/K+-ATPase) is the major autoantigen in AIG. Our work aimed to investigate the gastric H+/K+-ATPase-specific T helper 17 responses in AIG and serum interleukins (IL) -17 cytokines subfamily in AIG patients, in healthy subjects (HC), and in patients with iron deficient anemia (IDA) without AIG. We analyzed the activation of gastric lamina propria mononuclear cells (LPMCs) by H+/K+-ATPase, as well as the IL-17A, IL-17F cytokine production in eight patients with AIG and four HC. Furthermore, we compared serum levels of IL-17A, IL-17F, IL-21, IL-17E, IL-22, and IL-23 in 43 AIG patients, in 47 HC and in 20 IDA patients without autoimmune gastritis. Gastric LPMCs from all AIG patients, but not from HC, were activated by H+/K+-ATPase, proliferated and produced high levels of IL-17A, IL-17F. AIG patients have significantly higher serum IL-17A, IL-17F, IL-21, IL-17E (393.3 ± 410.02, 394.0 ± 378.03, 300.46 ± 303.45, 34.92 ± 32.56 pg/ml, respectively) than healthy subjects (222.99 ± 361.24, 217.49 ± 312.1, 147.43 ± 259.17, 8.69 ± 8.98 pg/ml, respectively) and than IDA patients without AIG (58.06 ± 107.49, 74.26 ± 178.50, 96.86 ± 177.46, 10.64 ± 17.70 pg/ml, respectively). Altogether, our results indicate that IL-17A and IL-17F are produced in vivo in the stomach of AIG patients following activation with H+/K+-ATPase and that serum IL-17A, IL-17F, IL-21, IL-17E levels are significantly elevated in AIG patients but not in patients without AIG. These data suggest a Th17 signature in AIG and that IL-17A, IL-17F, IL-21, IL-17E may represent a relevant tool for the AIG management.